Candidemia Among Pediatric Cancer Patients: Clinical Features, Resistance Pattern, and Treatment Outcome - Youssef Madney; Reham Khedr; Hanfy Hafiz; Naglaa Adel; Mervat Elanany; Khaled Alsheshtawi; Lobna Shalaby; Alaa El Haddad (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Candidemia presents a significant challenge for pediatric cancer patients, especially with the increasing incidence of echinocandin-resistant Candida and breakthrough candidemia. Recent data highlight a notable shift in the epidemiology of candidemia, with a predominance of non-albicans species, such as C. glabrata, C. parapsilosis, and C. tropicalis, over C. albicans. The incidence of invasive disseminated candidiasis among children ranges from 9% to 10% and is linked to mortality rates between 21% and 48%. Data on children with cancer with candidemia is still scarce, and despite advancements in antifungal treatment, mortality rates from candidemia among pediatric cancer patients remain high. Methods This retrospective study, conducted from 2014 to 2020 at the Children’s Cancer Hospital in Egypt, examined 350 pediatric patients with candidemia. This study evaluated the clinical characteristics, antifungal resistance patterns, and treatment outcomes of these patients, providing valuable insights to inform evidence-based strategies and enhance survival rates. Results The median age was four years, with 54% having hematological malignancies and 46% having solid tumors. The main clinical features included neutropenia (80%), prolonged corticosteroid use (43%), central venous lines (57%), and ICU admissions (44%). Non-albicans Candida accounted for 71% of isolates, with C. tropicalis and C. parapsilosis being the most common species. Chronic disseminated candidiasis was reported in 9% with liver and spleen being the most affected organs, while the brain and retina were the least affected. Invasive candidiasis was the attributable cause of death in 24% (n=7) of patients. Breakthrough candidemia was observed in 27% of patients, predominantly among those receiving echinocandin prophylaxis. Mortality was reported in 32 patients (33%), with breakthrough candidemia causing death in eleven (11%) patients. Resistance rates were notable: 15% to fluconazole, 6% to liposomal amphotericin-B, 5% to echinocandins, and 3% to voriconazole. The mortality rate was significantly higher in patients with resistant Candida infections (28 deaths) compared to those with sensitive infections. The overall 30-day mortality rate was 24%. Key predictors of mortality included delayed antifungal therapy, delayed catheter removal for source control, Echinocandin resistance, and septic shock requiring ICU admission. Conclusion Candidemia represents a serious threat to pediatric cancer patients, with delayed diagnosis or treatment significantly increasing the risk of mortality. Echinocandin-resistant candidemia, breakthrough candidemia, and chronic disseminated candidiasis pose significant challenges for pediatric cancer patients and are associated with a higher mortality rate. Antifungal stewardship, achieved through prompt diagnostics and treatment, is essential for enhancing outcomes in this high-risk group.